Tridax procumbens: A Herbal Nano Formulation for Cancer Therapy - Ramya Devi, D.; Sandhya, P.; Subhashri, S.; Vedha Hari, B.N. (Asian Journal of Chemistry, 2014)
The therapeutic values of commonly available plants are of more interest due to its beneficial pharmacological activities. Tridax procumbens, an Asteraceaeous member is a most commonly available weed and pest plant in native topical Americas and few tribal parts of India. This plant has several medicinal properties. Its fresh leaf juice is used to cure wounds, to stop bleeding and also used as a hair tonic. The objective of the present work is to extract the leaves of T. procumbens by maceration process using water and to identify the presence of various phyto-chemical constituents. The crude extract was developed into polymer-herbal nanoparticle by solvent evaporation process using polyvinyl pyrrolidine (PVP) and characterized for its size and stability. The crude herbal extract and its nanoparticle formulation were evaluated for antioxidant and antiinflammatory potential through in vitro methods and anticancer activity evaluated through MTT assay against HeLa cell lines.